APOE4 carriership status influences [11C]PiB white matter retention in cognitively healthy older adults - Tato-Fernández Claudia; Ekblad Laura L.; Bucci Marco; Tuisku Jouni; Parkkola Riitta; Helin Semi; Rinne Juha O.; Snellman Anniina (Elsevier BV, 2026)
Purpose: The objective of this study was to assess whether APOE4 carriership status affects white matter (WM) [11C]PiB positron emission tomography (PET) retention in cognitively healthy older adults, as a potential indicator of myelin integrity.
Methods: We explored WM [11C]PiB retention of 101 participants (non-carriers, n = 40; APOE3/4 carriers, n = 40; APOE4/4 carriers, n = 21) and its association with fractional anisotropy, a diffusion tensor imaging measure reflecting WM microstructure. WM [11C]PiB retention was assessed in voxel-wise analysis and within normal-appearing white matter (NAWM) and white matter hyperintensities (WMHs) as regions-of-interest.
Results: [11C]PiB retention was lower in WMHs than NAWM (pt-test < 0.001). In NAWM, APOE4/4 and APOE3/4 carriers showed reduced [11C]PiB retention compared to non-carriers (pANCOVA = 0.040, among all groups), while there were no significant differences in [11C]PiB retention within regions of WMHs (pANCOVA = 0.11). APOE4/4 carriers had lower WM [11C]PiB retention than non-carriers in voxel-wise analysis (pFWE < 0.05). WM [11C]PiB retention was not associated with fractional anisotropy, suggesting different pathological pathways.
Conclusion: A decrease in NAWM [11C]PiB retention is suggestive of myelin damage prior to the onset of cognitive decline in APOE4 homozygotes.